Detection of Carbapenemase-Producing Enterobacterales: A Comparative Analysis of Available Phenotypic Methods - Tiwari, Neha; Jahan, Noor; Singh, Snehil; Singh, Nidhi; Mishra, Nikita; Gupta, Prakhar; Pandey, Anand (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Background: Carbapenems serve as a critical last-line defence against infections from multidrug-resistant Enterobacterales. The increasing prevalence of CRE (carbapenem-resistant Enterobacterales) poses significant challenges in clinical settings. This greatly complicates the handling of gram-negative bacilli (GNB) infections and represents a significant global health threat. Aim: This study evaluates and contrasts different phenotypic techniques used to identify carbapenemase-producing Enterobacterales isolated from various clinical samples. Objectives: To compare the accuracy and reliability of Combined Disc Test (CDT) and Modified Carbapenem Inactivation Method/EDTA - Carbapenem Inactivation Method (mCIM/eCIM) in identifying Metallo-beta-lactamase (MBL)-producing Enterobacterales. Methods: All clinical specimens submitted for culture and sensitivity testing at the Department of Microbiology were analysed to isolate and identify Enterobacterales. Carbapenemase production was assessed through using the phenotypic CDT Confirmation was carried out using the mCIM and eCIM in accordance with Clinical and Laboratory Standards Institute (CLSI) guidelines. Results: During a two-year period, 254 strains of Enterobacterales were isolated. Among those, 80/254 (31.49%) isolates exhibited resistance to the Imipenem (IMP) disc. The CDT identified 30/80 (37.5%) isolates as serine carbapenemase producers and 50/80 (62.5%) isolates as MBL producers. In comparison, the mCIM/eCIM methods detected 26/80 (32.5%) isolates as serine carbapenemase producers, 48/80 (60.0%) isolates as MBL producers, and 6/80 (7.5%) isolates were tested negative for carbapenemase production. Conclusion: This study evaluates the precision and effectiveness of the mCIM/eCIM and CDT methods for identifying CRE. The combination of the mCIM and eCIM tests may be a more reliable phenotypic method for detecting carbapenemase compared to the CDT.